Design and methodology of a mixed methods follow-up study to the 2014 Ghana Demographic and Health Survey - Sarah Staveteig; Richmond Aryeetey; Michael Anie-Ansah; Clement Ahiadeke; Ladys Ortiz (Taylor & Francis Group, 2017)
Background: The intended meaning behind responses to standard questions posed in large-scale health surveys are not always well understood. Systematic follow-up studies, particularly those which pose a few repeated questions followed by open-ended discussions, are well positioned to gauge stability and consistency of data and to shed light on the intended meaning behind survey responses. Such follow-up studies require extensive coordination and face challenges in protecting respondent confidentiality during the process of recontacting and reinterviewing participants. Objectives: We describe practical field strategies for undertaking a mixed methods follow-up study during a large-scale health survey. Methods: The study was designed as a mixed methods follow-up study embedded within the 2014 Ghana Demographic and Health Survey (GDHS). The study was implemented in 13 clusters. Android tablets were used to import reference data from the parent survey and to administer the questionnaire, which asked a mixture of closed- and open-ended questions on reproductive intentions, decision-making, and family planning. Results: Despite a number of obstacles related to recontacting respondents and concern about respondent fatigue, over 92 percent of the selected sub-sample were successfully recontacted and reinterviewed; all consented to audio recording. A confidential linkage between GDHS data, follow-up tablet data, and audio transcripts was successfully created for the purpose of analysis. Conclusions: We summarize the challenges in follow-up study design, including ethical considerations, sample size, auditing, filtering, successful use of tablets, and share lessons learned for future such follow-up surveys.